Internetowa reklama wyborcza a reklama w „starych” mediach w polskich kampaniach parlamentarnych w latach 2001-2015 - Jakub Żurawski (Ksiegarnia Akademicka Publishing, 2021)
Internet Electoral Advertising and Advertising in the “Old” Media in Polish Parliamentary Campaigns from 2001 to 2015